Annual report and accounts for the year ended ... - Electricity Corporation of Nigeria (Lagos, Nigeria : Electricity Corporation of Nigeria, 1960)
This is the annual report and statement of account of the Electricity Corporation of Nigeria which was later named Nigerian Electric Power Authority (NEPA).
oif 15/04/2019
Ref.
Keywords: Electric utilities; Nigeria